THE EFFECTIVENESS OF INQUIRY BASED SCIENCE LEARNING BY FUTURE TEACHER OF ELEMENTARY SCHOOL - Rosnita, Rosnita (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The aim of this research is to investigate the effectiveness of science inquiry-based modul with authentic assessment to develop students’ inquiry skills and critical thinking. This research employed a quasi experiment method with pretest-posttest control group design. This research is conducted on 5th grade of one of Junior Elementry School in Pontianak, by using 2 classes as a sample. The data was collected by using inquiry skills observation sheets, and interview. The result shows that the mean of inquiry skills scores of experiment group is higher than the control group, and the significance score from using t-test is (0.00) < 0.05, which means there is a difference of inquiry skills in the experiment and control group. Score of N-gain shows that the mean of experiment group’s inqury skills score after the treatment, is higher than control group. It concludes that science learning by using inquiry-based is effective to develop students’ inquiry skills.